Paleomagnetic and paleoenvironmental implications of magnetofossil occurrences in late Miocene marine sediments from the Guadalquivir Basin, SW Spain - Larrasoaña, Juan C.; Liu, Qingsong; Hu, Pengxiang; Roberts, Andrew P.; Mata, Pilar; Civis, Jorge; Sierro, Francisco J.; Pérez-Asensio, José N. (Frontiers in Microbiology, 2014)
Although recent studies have revealed more widespread occurrences of magnetofossils in pre-Quaternary sediments than has been previously reported, their significance for paleomagetic and paleoenvironmental studies is not fully understood. We present a paleo- and rock-magnetic study of late Miocene marine sediments recovered from the Guadalquivir Basin (SW Spain). Well-defined paleomagnetic directions provide a robust magnetostratigraphic chronology for the two studied sediment cores. Rock magnetic results indicate the dominance of intact magnetosome chains throughout the studied sediments. These results provide a link between the highest-quality paleomagnetic directions and higher magnetofossil abundances. We interpret that bacterial magnetite formed in the surface sediment mixed layer and that these magnetic particles gave rise to a paleomagnetic signal in the same way as detrital grains. They, therefore, carry a magnetization that is essentially identical to a post-depositional remanent magnetization and that we term a bio-depositional remanent magnetization (BDRM). Some studied polarity reversals record paleomagnetic directions that appear to be delayed by 60-70 kyr. Magnetofossils in these cases are interpreted to carry a biogeochemical remanent magnetization (BGRM) that is locked in at greater depth in the sediment column. A sharp decrease in magnetofossil abundance toward the middle of the studied boreholes broadly coincides with a major rise in sediment accumulation rates near the onset of the Messinian salinity crisis (MSC), an event caused by interruption of the connection between the Mediterranean Sea and the Atlantic Ocean. This correlation appears to have resulted from dilution of magnetofossils by enhanced terrigenous inputs that were driven, in turn, by sedimentary changes triggered in the basin at the onset of the MSC. Our study highlights the importance of magnetofossils as carriers of high-quality paleomagnetic and paleoenvironmental signals.